Andean Women’s Persistence Amidst Racialized Gendered Impoverishment, Capitalist Incursions, and Post-conflict Hauntings - Távara, Gabriela; Lykes, M. Brinton (Frontiers in Psychology, 2022)
Throughout the last four decades Andean women from the highland communities of Peru have been significantly affected by ongoing neoliberal capitalist development and patriarchal structures. These intersecting violence(s) took on more horrific dimensions during the Peruvian armed conflict (1980-2000) and have contributed to multiple psychosocial sequalae that linger in the daily lives on these communities as “ghostly matters”. Seeking to face these sequelae in a context of ongoing material impoverishment, Andean women from highland communities have initiated multiple associations or economic collective projects. The authors accompanied a group of women who formed a knitting association and facilitated a feminist participatory action research (FPAR), creating opportunities through which these women could engage in action-reflection processes towards enhancing their association. Twelve women from this FPAR process agreed to be interviewed by the first author who sought to explore their understandings about the processes of forming their association in this post-conflict context and the challenges they were facing. Interview transcripts were analyzed using Charmaz's constructivist grounded theory coding strategy . The findings reveal multiple challenges for women’s collaborative work created by ongoing racialized gendered violence and its intra- and interpersonal effects. Moreover, the findings confirmed that capitalist development dynamics, and, more particularly, resources introduced by agents from outside the community bring both gains and losses for Andean women. The latter reported having learned skills that allowed them to better insert themselves in a market economy, but that these new activities were displacing more community-based Indigenous practices and traditions. Finally, this study reveals that the wounds created by the armed conflict generated multiple forms of silence that prevent Andean peasants from openly expressing their desires. Despite this, the women in this FPAR process and participants in these interviews are engaging in action-based responses through which they are overcoming some of these challenges and sustaining their association. The article concludes with a discussion of the implications for mental health professionals and activist-scholars working with Indigenous communities affected by armed conflict by underscoring the limitations of interventions based exclusively on the spoken word and arguing for action-based approaches that draw on bottom-up knowledge and practices.